Pathogenesis and Anatomical Features of Children With Congenital Cleft Lip and Palate. (Texas Journal of Medical Science, 2023)
For the treatment of children with congenital cleft lip and palate (CCLP), it is necessary to periodically study the dynamics of physical development. The development of the craniofacial region in children with CCLP after surgical manipulations is a widely discussed topic. The study of the growth of the facial skeleton and, in general, the entire physique of a child can be a theoretical and methodological basis for the development and improvement of morphometric methods of diagnostics and reconstruction in medicine and predict the appearance of secondary defects in the craniofacial region